Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1001/archdermatol.2008.562
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Topical Regimen of 5-Fluorouracil, 0.5%, Cream for the Treatment of Actinic Keratoses

Abstract: tempted to validate a tool that can be used to determine the prevalence of hyperpigmentation disorders in Chinese women. We refined the language and syntax by consulting with Chinese teachers, and then we administered the questionnaire to a focus group to maximize comprehensibility. The results of the study in 69 female Chinese subjects show that this questionnaire is valid for selfreporting of lentigines and PIH. Limitations include lack of a broad sample (most of the patients were middle-aged women) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…56 Investigators reported that electronically monitored adherence only declined from 92% to 82% over 4 weeks in a small study (n = 20) of a topical AK therapy. 57 The investigators proposed that the presence of the AEs (79% of patients) may have actually increased adherence by providing evidence of medication efficacy and that patients may have understood that the discomfort was temporary because treatment concluded at 4 weeks. 57 Adherence requires success at multiple levels, including mutual agreement between the patient and health care professional on the treatment plan, redemption of the initial prescription, and its correct use at home.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Investigators reported that electronically monitored adherence only declined from 92% to 82% over 4 weeks in a small study (n = 20) of a topical AK therapy. 57 The investigators proposed that the presence of the AEs (79% of patients) may have actually increased adherence by providing evidence of medication efficacy and that patients may have understood that the discomfort was temporary because treatment concluded at 4 weeks. 57 Adherence requires success at multiple levels, including mutual agreement between the patient and health care professional on the treatment plan, redemption of the initial prescription, and its correct use at home.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
“…57 The investigators proposed that the presence of the AEs (79% of patients) may have actually increased adherence by providing evidence of medication efficacy and that patients may have understood that the discomfort was temporary because treatment concluded at 4 weeks. 57 Adherence requires success at multiple levels, including mutual agreement between the patient and health care professional on the treatment plan, redemption of the initial prescription, and its correct use at home. A study of Danish national pharmacy records reported that 30% of approximately 300 patients with dermatologic conditions did not purchase their newly prescribed medication.…”
Section: Adherence To Treatment Regimensmentioning
confidence: 99%
“…Erntoft et al (32) and Shergill et al (33) used patient recall as a measurement of adherence and persistence (32,33), whereas Yentzer et al calculated adherence using the medication event monitoring system (MEMS), which is a monitoring cap hidden on the treatment vessel (34). The clinical trials identified within the search (35)(36)(37)(38)(39)(40) provided either drop-out rates, discontinuation rates or adherence rates; however, no definition of or calculation of adherence was provided in the published information on these studies.…”
Section: Measures Of Adherencementioning
confidence: 99%
“…Two real-world studies measured patients' overall adherence and persistence to several topical AK therapies (32,33) and a third measured patients' adherence to 5-FU 0.5% (34).…”
Section: Adherence In Real-world Studiesmentioning
confidence: 99%
“…Irritation may remind patients to use medication; some of the best adherence to topical treatment was seen in a study of 5-fluorouracil for actinic keratosis, with a mean adherence rate of 86%. 39 Although patients with actinic keratoses are different from patients with acne (more likely to be more mature, older, and possibly more motivated to spare themselves surgery or other treatments), the good adherence in this population shows that a high degree of irritation does not mean that adherence will be poor. The effects of tolerability on adherence are not necessarily predictable, and care must be taken to avoid the propagation of unsubstantiated dogma in the scientific literature.…”
mentioning
confidence: 91%